ALKALOHALOPHILIC BACTERIA OF THE FAMILY BACILLACEAE IN THE LAKES OF THE BADAIN JARAN DESERT (CHINA) - E. B. Erdyneeva; A. A. Radnagurueva; N. L. Belkova; Z. B. Namsaraev; E. V. Lavrentieva (Вавиловский журнал генетики и селекции, 2018)
The Badain Jaran desert is located in the western part of Inner Mongolia (China) in the Alashan Highland. The investigated soda-salt lakes combine high pH (more than 9) and mineralization (up to 400 g/dm3), where conditions for the development of an alkali-halophilic microbial community are created. The purpose of our work was to isolate and study pure alkali-halophilic microorganisms in the lakes of the Badain Jaran desert. From the accumulative cultures of the cortex salt and the microbial mats of the lakes of the Badain Jaran desert, pure cultures belonging to the family Bacillaceae (the phylum Firmicutes) were isolated and described. With the help of biochemical methods, the ecological and physiological properties of the isolated bacteria were determined. The isolated bacteria exhibit the properties of alkalophiles and obligate alkalophiles and develop at pH 7–10.5, the optima ranging from 9 to 10. With respect to the concentration of NaCl, the strains showed the properties of obligate halophiles and extreme halophiles. With respect to temperature, the isolated microorganisms are mesophiles growing at 10–50 °C, the optimal growth being at 30–40 °C. With respect to the substrates used, the isolated cultures are noted for extensive metabolic activity and, when in their natural habitats, are supposedly active participants of the destruction of organic matter. To study the hydrochemical indicators of water, the following methods were used: atomic emission spectrometry with inductively coupled plasma, ion chromatography and capillary electrophoresis. As a result, it was found that a sodium cation and anions of carbonate, bicarbonate of chlorine and sulphate dominate in the soda-salt lakes of the Badain Jaran desert in a multicomponent composition. The results obtained broaden the notion of the diversity and ecological significance of bacteria in the extreme natural ecosystems of the Badain Jaran desert. The isolated strains are of interest for biotechnology as producers of enzymes resistant to high pH and mineralization.